PENGARUH TABUNGAN DAN DEPOSITO TERHADAP HARGA SAHAM PADA PERBANKAN BUMN DAN BUMD YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Dewi Selviani Yulientinah; Siti Aidah Latifah (LAND JOURNAL, 2026)
The stock price serves as a key indicator for evaluating a company’s performance,including that of firms operating in the banking sector. But in practice, the stock price is not only influenced by profit performance, However,performance is also shaped by a range of other factors,including the composition of third-party funds such as savings and time deposits. As financial intermediaries,banks mobilize public funds through these deposit instrument,whichin turn can influence investor confidence and ultimately affect the market value of the bank’s share. This study to analyze the effect of savings and deposits on stock prices in state-owned banks (BUMN) and regionally-owned banks (BUMD). The method used in this research is quantitative by utilizing secondary data obtained from financial reports and stock price reports for the 2021-2024 period,processed and interpreted using IBM SPSS Statistics version 27. The study used several tools to analyze the data, such as checking if the data follows a normal curve, finding the relationship between variables, using a multiple linear regression model, calculating how well the model explains the data, and performing t and F tests. The t test found that savings have a somewhat significant positive impact on stock prices, but time deposits do not have a similar effect. The F test results indicated that savings and time deposits collectivitely evert a positive and significant influence on stock prices.